THE INFLUENCE OF JOB CRAFTING DIMENSION ON EMPLOYEE ENGAGEMENT - BEI YING, GAN (Universiti Malaysia Sarawak (UNIMAS), 2021)
This study aims to determine the relationship between dimension in job crafting (task crafting, relational crafting and cognitive crafting) and employee engagement in manufacturing industry. The theory used in this study is Job- Demands- Resources (JDR) model. A survey methodology was used in this study. The research involve the utilization of questionnaire which involve among 92 employees from manufacturing industry in Johor Bahru, Johor. The relationship between dimension in job crafting and employee engagement was analyzed by using Spearman Correlation Coefficient. The dominant dimension that affecting employee engagement was identified by using Multiple Regression Analysis. The result shows that there is a strong positive relationship between task crafting and employee engagement and very strong positive relationship occur between relational crafting and cognitive crafting with employee engagement. The result also shows that cognitive crafting is the dominant dimension of job crafting that affecting employee engagement. Hence, from this study the organization can consider implementing of practicing job crafting in order to improve employee engagement in the organization.